(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background Acute postoperative pain has adverse effects on the various physiological functions of the body.It can cause haemodynamicderrangement,delay in ambulation.In paediatric population it causes anxiety, apprehension & behaviour changes. Aims& objectives We conducted a randomized observational study to compare the efficacy of preoperative rectal diclofenac ,paracetamol & their combination for postoperative analgesia , haemodynamic stability, cost-effective ness, adverse effects in paediatric age group. , Material methods children (2– 12 yrs) undergoing minor surgical procedures were randomly allocated into 3 groups, of 30 patients each group A received diclofenac suppository2 mg/kg post induction . group B received paracetamol 20 mg/kg suppository post induction. Group C received combination of Diclofenac1mg/kg& paracetamol 10 mg/ kg suppositories 1 Pain was assessed by the “Hanallah pain scale” which denotes pain based on 5 parameters, systolic blood pressure, crying, movements, agitation (confused, excited), and complaints of pain. Conclusion We concluded that though , diclofenac sodium , paracetamol & their combination are good postoperative analgesics when given by rectal route in pediatric patients undergoing minor surgeries, combination group provides better analgesia than others when given by rectal route in pediatric patients in terms of haemodynamics, post-operative analgesia, cost-effective ness, adverse effects.